Promenade in Asia : After Kitsch, Cute : Beijing, Seoul, Tokyo, Taipei. - Asai, Toshihiro; Higuchi, Masaki (Tokyo : Shiseido Co. Ltd., 2001)
Each of Shiseido Gallery and Contemporary Art Center, Art Tower Mito holds its own project exhibition under the same theme "Promenade in Asia", meaning the four areas in East Asia : Japan, Korea, China and Taiwan. The exhibition "Promenade in Asia" was held twice in 1994 and 1997, organized by Shiseido Gallery. The first exhibition was a collaboration between a curator and artists, and in the second exhibition, plural curators worked together. This time, the exhibition is intended for communicatiions between the two museums. The single exhibition frequently tours around Japan, but two or more art centers have seldom held exhibitions simultaneously under the same theme. It is our sincere hope that this project will trigger an interchange among museums and a new trend of exhibtions.
Chung, Seoyoung ; Chu, Chiahua ; Hosoi, Atsushi ; Huang, Rui ; Rong Rong ; Iijima, Ai ; Kawakami, Wakako ; Ku, Shihyung ; Nishiyama, Minako ; Park, Hongchun ; Yao, Juichung ; Wang, Junjieh ; Wang, Qingsong ; Wang, Teyu
English-Japanese
Promenade in Asia : After Kitsch, Shiseido Gallery, Tokyo ; Contemporary Art Center Art Tower Mito, Mito-shi, August 10 - October 21, 2001
kunstcatalogus
Keywords: Azië; China; Japan; Korea; Taiwan